Determinants of ocular symptoms in postmenopausal women with dry eye - Stapleton, Fiona; Badarudin, Noor Ezailina; Jing, Jing You; Hampel, Ulrike; Eden, John; Raisin, Leanne; Williams, Jennifer; Chao, Cecilia; Blanka Golebiowski, Blanka (Association Of Research In Vision Ophthalmology (United States), 2015)
Purpose: Dry eye in women is more prevalent postmenopause and alterations in sex hormone levels may be implicated. This study explored the relationship between serum concentration of sex hormones and dry eye symptoms and ocular surface signs. Methods: The study involved 46 postmenopausal women diagnosed with non-Sjögrens dry eye and not taking hormone replacement therapy (mean age 64±5 years, 14±6 years since menopause). The following measurements were conducted at a single timepoint: Ocular symptoms (Ocular Surface Disease Index (OSDI) and Ocular Comfort Index (OCI)), tear function (non-invasive tear break-up time (NITBUT), tear osmolarity (TearLab), tear volume (Phenol Red Thread and Schirmer tests)), ocular surface staining and meibomian gland assessment using grading scales, ocular surface sensitivity (Cochet-Bonnet aesthesiometer) and venous blood collection. Serum concentrations of 17β-estradiol (E2), 3α-diol-G, DHEA-S and their ratios were determined using Enzyme-linked immunosorbent assay (ELISA). Univariate associations were examined using Spearman’s correlations and multiple linear regression analysis was subsequently used to examine predictors of dry eye symptoms. Results: Mean serum concentration of E2 was 10.8±19.7pg/ml, 2.10±2.77ng/ml of 3α-diol-G and 0.73±0.55μg/ml of DHEA-S. Mean symptoms scores were 27.0±18.1 (OSDI) and 40.3±8.4 (OCI). Only tear osmolarity and meibomian gland secretion quality were significant predictors in the OSDI model; this model explained 20% of the variance in the OSDI score (F(6, 39)=2.858, p=0.02, R2adj= 0.20). Eyelid vascularity and meibomian gland expressibility were significant predictors in the OCI dryness frequency model, explaining 29% of the variance in dryness frequency (F(6, 39)=4.015, p=0.003, R2adj=0.29). Although serum hormones were associated with symptoms scores on univariate correlations, E2, 3α-diol-G, DHEA-S or their ratios were not found to be significant predictors of ocular symptoms in the full multivariate model(p>0.05). Conclusions: Meibomian gland and lid variables are significant predictors of ocular symptoms in postmenopausal women with dry eye, but serum hormone levels were not shown to play a significant role in this study. These findings would suggest that meibomian gland disease underpins dry eye symptoms in this cohort and examination in a lager cohort is required may further elucidate the role of sex hormones in non-Sjögrens dry eye in postmenopausal women.